Grain size effect on shearing performance of copper foil: A polycrystal plasticity investigation. (March 2022) - Li, Xiao; Li, Xiucheng; Misra, R.D.K.; Chen, Zhanghua
Abstract: The existing experimental observations about the grain size effect on the shearing performance of copper foils lack material and mechanical interpretation. Hence, for the first time, the micro-blanking process of 100 μm thick polycrystalline aggregates with different grain sizes and microstructures has been simulated based on the crystal plasticity framework. The obtained results visually displayed the different deformation modes of the coarse- and fine-grained materials. The grain refinement was found to be conducive for maintaining the regularity in the sheared edge. The orientation effect played an important role in the shearing process. Additionally, a correlation between the repeatability of the punching force and grain size was qualitatively developed, and the microhardness of the deformed material was calculated based on the flow stress and compared with the previous measurements. Further, the limitations of the presented simulation approach have been elaborated in detail, with multiple guidelines provided for modification. The findings reported in this paper contribute to an in-depth understanding of the cross-scaled shearing performance of the copper foil and the importance of the grain size effect. Graphical abstract: Image 1 Highlights: Shearing performance of copper foil was predicted by crystal plasticity simulation. Coarse-grained foils have poor processing repeatability. Grain refinement is conducive to maintaining regularity in the sheared edge. Orientation effect played an important role in micro-shearing.